1980
DOI: 10.1002/ajh.2830080105
|View full text |Cite
|
Sign up to set email alerts
|

The decline in energetic metabolism with aging of the erythrocyte and its relationship to cell death

Abstract: Human erythrocytes were separated by buoyant density ultracentrifugation into fractions of progressively increasing mean cell age to measure the changes in glycolytic activity that occur during their 120-day life-span. The maximal activities of all glycolytic enzymes were shown to decline exponentially with cell age. Only three glycolytic enzymes exhibited a marked rate of decline with a tl/2 shorter than the cell life-span: hexokinase, aldolase, and pyruvate kinase. ganic phosphate), showed a fourfold decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
53
1

Year Published

1981
1981
1993
1993

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(60 citation statements)
references
References 18 publications
6
53
1
Order By: Relevance
“…This brings into question a commonly used criterion (17) for aged red cells, the loss of certain catalytic activities. Our studies show that the time-dependent conversion of band 4. lb to 4.la, predicted earlier by Sauberman et al (6), is a valid marker for cell senescence and may be a more valid criterion than the level of enzymatic activity.…”
Section: Discussionmentioning
confidence: 99%
“…This brings into question a commonly used criterion (17) for aged red cells, the loss of certain catalytic activities. Our studies show that the time-dependent conversion of band 4. lb to 4.la, predicted earlier by Sauberman et al (6), is a valid marker for cell senescence and may be a more valid criterion than the level of enzymatic activity.…”
Section: Discussionmentioning
confidence: 99%
“…They have consisted of separating red cells into fractions enriched with young cells or old cells employing density gradients (9-1 1) or osmotic fragility (1 2) and relating various biochemical parameters to the relative age of the cell fraction obtained. The most sophisticated analysis of the decline of enzyme activities during red cell aging using such data is that employed by Piomelli and his colleagues (9,13) in which red cells are separated by density. The logarithm of the enzyme activity of each fraction is then plotted against the probit of the cumulative fraction of the erythrocytes in the density fraction being examined.…”
Section: Discussionmentioning
confidence: 99%
“…The logarithm of the enzyme activity of each fraction is then plotted against the probit of the cumulative fraction of the erythrocytes in the density fraction being examined. Piomelli et al (9) and Seaman et al (13) fitted a straight line to the data using the method of least squares to the data, and took the slope as the half-life of the enzyme. Using essentially the same transient erythroblastopenia of childhood Turner et al (10) suggested that two exponentials fit data obtained with purine nucleoside phosphorylase and 6-phosphogluconate dehydrogenase better than did a single exponential.…”
Section: Discussionmentioning
confidence: 99%
“…For the assay of erythrocyte glycolytic intermediates, fresh whole blood was added immediately from the syringe to an equal volume of ice-cold 2 N perchloric acid, and the neutralized supernatant was stored at -200C. The levels of glucose-6-phosphate (Glu-6-P), fructose-6-phosphate (Fru-6-P), fructose-1,6-diphosphate (Fru-1,6-P2), and triose phosphates were measured by spectrofluorometric methods, and 2,3-DPG by spectrophotometry within the next 4-6 d, as described previously (17).…”
Section: Methodsmentioning
confidence: 99%